Exploring the planets : a memoir - Taylor, F. W. (Oxford Oxford University Press, 2016)
The planets fascinate us, and naturally we care about our own Earth, and things like how well we can forecast the weather and whether climate is really changing. Exploring the Planets offers a personal account on how the space programme evolved. It begins in the era of the first blurry views of our Earth as seen from space, and ends with current plans for sophisticated robots on places as near as our neighbours Venus and Mars and as far away as the rainy lakelands of Saturn's planet-sized moon Titan. Examining the scientific goals of these complex voyages of discovery, and the joys and hardships of working to achieve them. The Space Age is now about 50 years old and for those lucky enough to be part of it at its inception, it's filled a worklong lifetime. Today, several satellites around the Earth have studied the atmosphere and the climate using instruments on board that the author helped design and build. 'Deep space' missions were embarked upon to visit the planets: all of the major bodies (six planets, the Moon and minor bodies, asteroids and comets) of the classical Solar System have been scrutinised close-up by experiments built in various laboratories worldwide. Most of the narrative is based on the author's experiences at the world's space agencies, research labs, and conferences, and at other places as diverse as Cape Canaveral and No. 10 Downing Street--
Prelude -- Satellites and spires -- The gateway to the planets -- Voyage to Venus -- With Galileo to Jupiter -- Back to Oxford -- Forecasting weather and climate -- The ozone layer and other crises -- Mishaps at Mars -- Operation Saturn -- The days of the comet -- Return to the silent planet -- Marooned on Mercury -- Mars at last -- Ice on the moon -- A beginner's guide to the end of the world -- STanding at the edge of time -- Epilogue.
Includes index.
Keywords: Astrophysicists -- England -- Biography; Astrophysicists